Trabajo de parto con o sin analgesia epidural. Relación entre la duración y posibles complicaciones, en la Clínica Medilab de la ciudad de Loja. Periodo enero junio de 2014 - Ludeña Medina, María Soledad (2015)
This is a study based on comparison between the duration and possible complications of labor with or without epidural analgesia. An analytical, quantitative, prospective cross-sectional study was lead, with a universe composed of 51 pregnant women who attended in “Medilab” clinical for the end of her pregnancy for normal birth, either using or not epidural analgesia. This study is about to compare the duration of labor and possible complications in primiparous or multiparous patients receiving or not epidural analgesia during labor. The population studied was analyzed with different variables previously established, using the data collection sheet that allowed to investigate and gather information that could be tabulated and then examined for obtain statistical data and finally provide results. Most users ended their labor without epidural analgesia in a ratio 1.5 to 1, being in most of them multiparous women belonging to the highest percentage. The duration of labor with epidural analgesia lasted approximately 20-40 minutes more than average, mainly in primiparous women. No complications occurred during the use of epidural analgesia on labor, except for the presence of postpartum headache and pain at the puncture site. KEYWORDS: labor, epidural analgesia.